Faktor-Faktor yang Mempengaruhi Masa Studi Mahasiswa Prodi Pendidikan Bahasa Jawa FBS UNY (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
This study aims at testing hypotheses formulated from theoretical studies. The hypotheses stated that the thesis supervisor, gender, and motivation affected the length of the thesis writing process and the Grade Point Average (henceforth: GPA), as well as impacting the study period. It is a quantitative research using mediation effect analysis (path analysis methods). In this study, there was no sampling as all populations were taken as respondents. Respondents in this study were 98 students of the Javanese education study program, Faculty of Language and Arts, Yogyakarta State University, Indonesia (PPBJ FBS UNY). The results showed that there was no significant influence of thesis consultation processes and motivation on the length of the thesis writing, there was no significant influence of thesis supervisor and motivation using the length of the thesis writing period on the study period, and there was no significant influence between gender and motivation of gaining higher GPA, however, yet, there was a significant direct influence of gender on GPA and motivation of gaining higher GPA, there was no significant influence of gender and motivation using GPA on the study period, however, there was a significant direct influence of gender on the study period, and there was a significant direct influence of the length of the thesis writing and GPA on the study period. Related to the findings of the research above, it is necessary to make various efforts so that students' intrinsic motivation is more awakened so that learning achievement will be better, and thesis duration and the study period is shorter.